PERHITUNGAN KETEBALAN BAHAN KOMPOSIT KARET ALAM TIMBAL OKSIDA UNTUK PROTEKSI RADIASI SINAR - X 100 Kev - Gunarwan Prayitno (BATAN, 2013)
The Thickness Calculation Of Lead Oxide Natural Rubber Composite For X-Ray Rodietion Protection. The thickness calculation of lead oxide natural rubber composite for x-ray radiation protection has been done for 100 kev energy x-ray. The calculation is to obtain the thickness of reaietiou protection that was safe for environment or worker who works in radiation field. The calculation of absorption strength of lead oxide natural rubber composite is started by lead oxide composite 550 part per one hundred rubber (pphr) until 1000 part per one hundred rubber. the lead okside natural rubber composite thickness to be calculated is 2.5 mm. The result of calculation shows that the thickness of substance lead oxide natural rubber composite was safe for environment or worker who works in radiation field, if the 550 part per one Iwndrecl rubber lead oxide was mixed with natural rubber. The value of absorption strength on 550 pert per one hundred rubber is standart permitted. Perhitungan ketebalan Bahan Komposit Karet Alam Timbal Oksida Untuk Proteksi Radiasi Sinar-x 100 Ke